2016
DOI: 10.5539/sar.v5n2p15
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Dry Common Beans Trade in Lusaka, Zambia: A Trader’s Perspective

Abstract: <p>This study was designed to analyze drivers of dry common beans trade in Lusaka, Zambia. Specifically, the study analyzed the effect of common bean grain characteristics on bean market price. Data was collected using structured questionnaires from 225 traders stationed in three markets namely: Soweto, Chilenje and Mtendere.</p>Using hedonic pricing, the findings reveal that medium sized grain was an important characteristic which significantly affected the pricing of common bean. For instance, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…In addition to their high yield potential, small-and medium-seeded beans are resistant to several diseases devastating the large-seeded beans such as angular leaf spot, anthracnose, rust, bean golden yellow mosaic virus and bean common mosaic virus and possess genes and high level of resistance to drought stress [6]. However, large-seeded Andean beans are the most widely grown in Eastern Africa because they are preferred by farmers and consumers for their seed quality and often fetch higher prices [5,7]. Andean genotypes possess a narrow to moderate genetic base especially for disease resistance and yield potential and thus, threatening progress toward improvements for those traits [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their high yield potential, small-and medium-seeded beans are resistant to several diseases devastating the large-seeded beans such as angular leaf spot, anthracnose, rust, bean golden yellow mosaic virus and bean common mosaic virus and possess genes and high level of resistance to drought stress [6]. However, large-seeded Andean beans are the most widely grown in Eastern Africa because they are preferred by farmers and consumers for their seed quality and often fetch higher prices [5,7]. Andean genotypes possess a narrow to moderate genetic base especially for disease resistance and yield potential and thus, threatening progress toward improvements for those traits [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Kenya [22] identified grain colour, cooking time, taste, grain size and availability of beans as significant factors underlying consumers' preferences. Similarly, a study in Zambia [23] reveals grain size and colour to influence consumers' preferences.…”
Section: Consumer Behaviour Theorymentioning
confidence: 98%
“…Thirty-two inter-racial and inter-gene pool populations were developed from crosses among Middle American (Mesoamerican) and Andean gene pool cultivars to broaden the genetic base of commercial cultivars, and take advantage of attributes of both gene pools. In addition to high yield potential of Middle American cultivars, they are resistant to major diseases of the Andean gene pool counterparts, and possess genes for drought resistance; while the Andean cultivars are the most preferred in Africa for their seed quality, and thus fetch higher prices in local markets (Welsh et al, 1995;Singh et al, 2002;Sichilima et al, 2016).…”
Section: Marker-assisted Gamete Selection For Multiple Disease Resistmentioning
confidence: 99%